Targeting Stress Sensor Kinases in Hepatocellular Carcinoma-Infiltrating Human NK Cells as a Novel Immunotherapeutic Strategy for Liver Cancer - Zecca, Alessandra; Barili, Valeria; Olivani, Andrea; Biasini, Elisabetta; Boni, Carolina; Fisicaro, Paola; Montali, Ilaria; Tiezzi, Camilla; Dalla Valle, Raffaele; Ferrari, Carlo; Cariani, Elisabetta; Missale, Gabriele (Frontiers in Immunology, 2022)
NK-cells may become functionally exhausted entering hepatocellular carcinoma and this has been associated with tumor progression and poor clinical outcome. Hypoxia, low nutrients, immunosuppressive cells and soluble mediators characterize the intratumor microenvironment responsible for metabolic deregulation of infiltrating immune cells, as NK-cells. HCC-infiltrating NK-cells from patients undergoing liver resection for HCC, were sorted and genome-wide transcriptoming profiling was obtained. We have identified a marked general upregulation of gene expression profile along with metabolic impairment of glycolysis, OXPHOS and autophagy as well as NK-cells functional defects. Targeting p38 kinase, a stress responsive MAPK, we could positively modify metabolic profile of NK-cells with functional restoration in terms of TNF-a production and cytotoxicity. We found a metabolic and functional derangement of HCC-infiltrating NK-cells that is part of the immune defects associated with tumor progression and recurrence. NK-cell exhaustion due to the hostile tumor-microenvironment may be restored with p38 inhibitors with a selective mechanism that is specific for tumor-infiltrating not affecting liver-infiltrating NK-cells. These results may represent the basis for the development of a new immunotherapeutic strategy, to integrate and improve the available treatments for HCC.